Chemical constituents from kernel of calophyllum inophyllum / Nurul Nabilah Shafiei - Shafiei, Nurul Nabilah (2019)
In this project, the chemical constituents from the plant species, Calophyllum inophyllum was carried out. Calophyllum inophyllum belongs to the genus of Calophyllum, is grouped into the family of Guttiferae. The kernel of Calophyllum inophyllum were extracted and isolated to obtain its chemical constituents. Phytochemical study on the hexane crude extract of the kernel of Calophyllum inophyllum yielded one triterpenoids, and one coumarin. The compounds isolated were identified as friedelin and calopolyanolide B. The homogeneity of isolated compounds was established by TLC, as there was no interference of spot or peak in chromatograms were recorded. For detailed structure elucidation, UV-Vis, IR, one dimensional 1H NMR, 13C NMR and MS spectra were recorded for specific structure elucidation.